Mechanisms of RNA N6-Methyladenosine in Hepatocellular Carcinoma: From the Perspectives of Etiology - Lu, Jiahua; Qian, Junjie; Yin, Shengyong; Zhou, Lin; Zheng, Shusen; Zhang, Wu (Frontiers in Oncology, 2020)
N6-Methyladenosine (m6A) is the commonest RNA internal modification in eukaryotic messenger RNAs (mRNAs), and its regulation at post-transcriptional level in both mRNAs and noncoding RNAs has been widely studied, including alternative splicing, stability, translation efficiency, nucleus export and degradation, which are implicated in a series of physiological or pathological activities. Recently, the significance of m6A methylation has been identified in both virus hepatitis and non-alcohol fatty liver disease (NAFLD), which are major risks in the development of hepatocellular carcinoma (HCC). Given the high incidence and mortality of HCC worldwide, it is of great importance to elucidate the mechanisms underlying HCC initiation and progression. As an emerging research focus, m6A has great potential to facilitate the understanding of HCC, especially from etiological perspectives. Thus, in this review we summarize recent progress of m6A mechanisms in terms of hepatitis virus, NAFLD and HCC, including their mechanisms and clinical applications.